Study of major compounds of essential oils by GC-MS for application in active Food packaging - Ribeiro-Santos, R. (2017)
Objective: The main volatile compounds of commercial EO were determined by gas chromatography coupled with mass spectrometry (GC-MS) with the aim of evaluate the most suitable EOs to be used as direct or indirect food additives